IDENTIFICATION OF QUERCETIN IN Echinops tenuisectus Family Compositae - ENAS JAWAD KHADEEM (College of Pharmacy / Mustansiriyah University, 2007)
This study is emphasized on the detection and identification of Quercetin Flavonoid in a newly studied, wild Iraqi plant, named Echinops tenuisectus of Compositae family. The medicinal importance of Quercetin on one hand, and the absence of any phytochemical investigation on tenuisectus specie of Echinops genus on the other hand, acquired this s importance. יstudy it Quercetin was identified in the plant extract of both, the aerial part's and the seed's extracts, by two chromatographic methods, first Thin Layer Chromatography (TLC) using TLC ready made Gf254 plates, UV detector at 254 nm, and tow different solvent systems in which the Rf value of the standard quercetin matched with the Rf value of the plant extract quercetin. HPLC was the other chromatographic method that proved the presence of quercetin in the plant extract by identical retention times. The result indicated that the quercetin content in the seed extract was higher than that in the plant extract of the aerial parts.